2018
DOI: 10.1021/acsenergylett.8b00920
|View full text |Cite
|
Sign up to set email alerts
|

Monolithic Photoelectrochemical Device for Direct Water Splitting with 19% Efficiency

Abstract: Recent rapid progress in efficiencies for solar water splitting by photoelectrochemical devices has enhanced its prospects to enable storable renewable energy. Efficient solar fuel generators all use tandem photoelectrode structures, and advanced integrated devices incorporate corrosion protection layers as well as heterogeneous catalysts. Realization of near thermodynamic limiting performance requires tailoring the energy band structure of the photoelectrode and also the optical and electronic properties of t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
380
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 376 publications
(386 citation statements)
references
References 26 publications
3
380
0
3
Order By: Relevance
“…This field has primarily focused on optimizing the photovoltage and current needed to split water efficiently, and these efforts have borne fruit with multiple works showing greater than 10 % efficient devices ,. Recently, attention has turned towards stability with most publications reporting on devices which exhibit stability for at least 24 hours ,.…”
Section: Figuresupporting
confidence: 83%
“…This field has primarily focused on optimizing the photovoltage and current needed to split water efficiently, and these efforts have borne fruit with multiple works showing greater than 10 % efficient devices ,. Recently, attention has turned towards stability with most publications reporting on devices which exhibit stability for at least 24 hours ,.…”
Section: Figuresupporting
confidence: 83%
“…The Department of Energy (DOE), United States, has set out an ultimate STH efficiency target of 25% for PEC water splitting based on photoelectrode systems with concentrated solar irradiation . The STH efficiency (η STH ) is defined as follows ηSTH=E01.23 V×jopmA cm2×fFEPin where E 0 = 1.23 V is the thermodynamic potential for water splitting under standard conditions, j op stands for the operating photocurrent density, f FE represents the Faradaic efficiency which is usually close to 100%, and P in is the power density of total incident solar irradiance. To achieve a high η STH , improving j op is crucial in which coupling efficient HER and OER electrocatalysts to semiconductor photoelectrodes play a significant role, as evidenced by many previous literature reports.…”
Section: Discussionmentioning
confidence: 99%
“…[23,24] The following year Seger et al reported a stabilized silicon-based photocathode with earthabundant MoS x hydrogen evolution catalyst using a thin Ti metal film as a protection layer. [26][27][28][29][30][31][32][33] Emerging materials such as Sb 2 Se 3 , [34,35] Cu 2 ZnSnS 4 (CZTS), [36][37][38] CuO, [39] CuInxGa (1-x) Se 2 (CIGS), [40] and CuBi 2 O 4 [41,42] have also been investigated with protective overlayers. [26][27][28][29][30][31][32][33] Emerging materials such as Sb 2 Se 3 , [34,35] Cu 2 ZnSnS 4 (CZTS), [36][37][38] CuO, [39] CuInxGa (1-x) Se 2 (CIGS), [40] and CuBi 2 O 4 [41,42] have also been investigated with protective overlayers.…”
Section: Photocathode Materials With Corrosion Protection Layersmentioning
confidence: 99%